Disparidades geográficas vs disparidades en habilidades de mujeres casadas en ciudades Latinoamericanas: Un modelo teórico - Paola L. Montero Ledezma (Institute for Advanced Development Studies (INESAD), 2019)
– While more married women in cities are part of the workforce, are they doing the jobs for which they have been prepared? How are the wages of this sector of the population formed? How does the spouse/partner's income or commuting costs affect their employment decisions? What is the structure of a Latin American city with formal and informal sectors? This article proposes a theoretical model that studies the interaction between geographical disparities (home-work) and disparities in skills of married women in Latin American cities. The intrinsic characteristic of informality in these markets is included and there is an analysis of how these disparities affect the results of this labor market in particular. After conducting a welfare analysis, and finding congestion and composition externalities, three economic policies are proposed to restore the social welfare of this economy. These are: (i) subsidy to the creation of vacancies, (ii) subsidy to transportation, and (iii) the creation of day-care centers, in order to restore social efficiency.
Keywords: J2; 330; female labor market; wages